2022
DOI: 10.1039/d2cp01702d
|View full text |Cite
|
Sign up to set email alerts
|

Silica dimerization in the presence of divalent cations

Abstract: The presence of divalent cations raises activation energy barrier and delays overall dimerization reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 44 publications
(68 reference statements)
2
18
0
Order By: Relevance
“…Among the anionic mechanisms, there are also differences in the reaction pathway associated with the arrangement of hydroxyl groups bonded with Si which are categorized as Anionic-I and Anionic-II. 1 Apart from the authors' investigation, the observational difference between neutral and anionic mechanisms has been demonstrated for silica oligomerization reaction by previous investigators. 2,3 Previous studies focused on the anionic pathway "Anionic Condensation → Si−OH rupture" and indicated the catalytic action of water in silica oligomerization.…”
Section: ■ Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Among the anionic mechanisms, there are also differences in the reaction pathway associated with the arrangement of hydroxyl groups bonded with Si which are categorized as Anionic-I and Anionic-II. 1 Apart from the authors' investigation, the observational difference between neutral and anionic mechanisms has been demonstrated for silica oligomerization reaction by previous investigators. 2,3 Previous studies focused on the anionic pathway "Anionic Condensation → Si−OH rupture" and indicated the catalytic action of water in silica oligomerization.…”
Section: ■ Introductionmentioning
confidence: 75%
“…Anionic condensation can be further categorized into anionic-I and anionic-II depending on the orientation of hydroxyl groups bonded with Si. 1 The complex pathway of anionic-I and anionic-II investigated in this paper has been shown in Figure 1a. The condensation process has been discussed extensively in our previous paper, 1 yet a brief outline of the step with a focus on hydrogen bonding has been presented in the following subsections for completeness of the process.…”
Section: ■ Simulation Methodologymentioning
confidence: 89%
See 3 more Smart Citations